Lifting the Burden: State Care of the Elderly and Labor Supply of Adult Children - Katrine Vellesen Løken; Shelly Lundberg; Julie Riise Kolstad (Institute for the Study of Labor (IZA), 2014)
In this paper, we use a 1998 reform in the federal funding of local home-based care for the elderly in Norway to examine the effects of formal care expansion on the labor supply decisions and mobility of middle-aged children. Our main finding is a consistent and significant negative impact of formal care expansion on work absences longer than 2 weeks for the adult daughters of single elderly parents. This effect is particularly strong for daughters with no siblings, and this group is also more likely to exceed earnings thresholds after the reform. We find no impacts of the reform on daughter's mobility or parental health, and no effects on adult sons. Our results provide evidence of substitution between formal home-based care and informal care for the group that is most likely to respond to the parent's need for care adult daughters with no siblings to share the burden of parental care. These results also highlight the importance of labor market institutions that provide flexibility in enabling women to balance home and work responsibilities.
Keywords: J14; J22; 330; formal and informal care; elderly; welfare state; women's career